THE STUDENTS’ PERCEPTION IN LISTENING ENGLISH OF THE ELEVENTH GRADE AT SMAN 1 TEMBILAHAN - Adi Wiluyo; Melda Yeni; Syafrizal (J-Shelves of Indragiri (JSI), 2025)
The importance of conducting this research is to introduce to students that through English listening lessons, they can get used to listening in English. The researcher conducted this study to gather information about students' perceptions of learning listening at SMAN 1 Tembilahan as an illustration of whether the implementation of learning listening can support students' English language proficiency. The design of this research was Descriptive Quantitative. The sample of this study consists of 60 students from the 11th grade, which is divided into 9 classes, from SMAN 1 Tembilahan. To determine the sample, the researcher used the systematic random sampling technique. The total population is 306 students. In collecting data, the researcher used questionnaire as a research tool. This questionnaire is used to determine students' perceptions of the implementation of listening lessons at SMAN 1 Tembilahan. The questionnaire used in the study is presented in 5 (five) alternatives commonly known as the Likert Scale. The research results indicate that students' perceptions of listening learning are less (55.82%), because 55.82% is still in < 55%. So, it can be concluded that students' perception of listening learning at SMAN 1 Tembilahan is less.